2019
DOI: 10.29252/nmce.3.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Historical Water-Supply Qanat Based On Fuzzy Method. An Application to the Isfahan Qanat (Isfahan, Iran)

Abstract: According to the geographical location of Iran, it enjoys both arid and semi-arid weather, which has been the cause of water shortage problems. Therefore, water has been one of strategic importance in Iran. When the population dramatically increased in ancient Iran, the demand for supplying water also increased simultaneously and brought about the need for the invention of a new way for supplying water from the ground by using gravity. This invention was named Qanat, and it has an important role for managing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…agriculture and mining). Chronic water shortages, with an annual average rainfall of less than 100 mm in this region have led to increasing changes in the hadrochemical parameters in the groundwater (Behzadi et al 2019;Shara et al 2023). However, most of the studied sites showed the values for the water quality within the permissible range of WHO and USEPA.…”
Section: Physicochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…agriculture and mining). Chronic water shortages, with an annual average rainfall of less than 100 mm in this region have led to increasing changes in the hadrochemical parameters in the groundwater (Behzadi et al 2019;Shara et al 2023). However, most of the studied sites showed the values for the water quality within the permissible range of WHO and USEPA.…”
Section: Physicochemical Characteristics Of Groundwatermentioning
confidence: 99%
“…By using standard deviation and correlation statistics, parameters that have greater correlation and amplitude than the others are determined, and then a specific number of optimal parameters is used instead of all the parameters and executed according to formula (2), in this study. This formula is set for three parameters, but in this research, it is applied for five parameters (including four bands of satellite imagery and surface evaporation values):…”
Section: Determining Optimal Bands For Relative Humidity and Temperaturementioning
confidence: 99%
“…Therefore, using remote sensing data to model climate data is a convenient and economical way. In recent years, the artificial intelligence approaches such as Coactive Neuro-Fuzzy Inference System (CANFIS), Adaptive Neuro-Fuzzy Inference System (ANFIS) which is hybrid of Artificial Neural Networks (ANN) and Fuzzy Inference System (FIS), Fuzzy-Logic (FL) [2], Radial Basis Neural Network (RBNN) which is a type of ANN, Support Vector Machines (SVM), Generalized Regression Neural Network (GRNN) which is a type of ANN, Genetic Algorithm (GA), Wavelet Transformation (WT) and Multi-Layer Perceptron Neural Network (MLPNN) have been significantly utilized in diverse fields such as modelling climate indicators [3][4][5][6][7][8][9][10][11][12][13][14][15]. In order to model the target data, researchers used terrestrial station data as inputs, which have many limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Shanghai traffic flow data was used to guide the study process, which includes data processing, cluster analysis and methodological comparisons. The results also showed that the Fuzzy C-Means (FCM) clustering algorithm is improved in both fuzzy membership and weight degree (Behzadi, Mousavi, & Norouzi, 2019;Cheng et al, 2020;Mahjoobi & Behzadi, 2022). In Qasim, Ziboon, and Falih (2018) conducted a study to analyze Transcad and GIS techniques to evaluate the transportation network in Nasiriyah city, Deir ez-Zor province.…”
Section: Introductionmentioning
confidence: 99%